Parental perceptions of oral health-related quality of life of Brazilian children and adolescents with autism spectrum disorder - Cancio, Viviane; Faker, Khawana; Tostes, Mônica Almeida (Brazilian Dental Science, 2019)
Objective:This paper aimed to assess the oral health-related quality of life (OHRQoL) of children and adolescents with autism spectrum disorder (ASD) using the parental/caregiver perceptions questionnaire (PCPQ). Materials and methods: Children aged 2 to 14 years, enrolled in the ACOLHER/PNE project at the Fluminense Federal University, RJ, Brazil, were assessed. The main independent variable was dental caries experience, diagnosed according to the World Health Organization (WHO) criteria. The variable was categorized as caries-free when dmft/DMFT=0 and caries experience when dmft/DMFT ? 1. Caregiver schooling, age, sex, and socioeconomic factors (Brazilian minimum wage – BMW) were the other independent variables. Quality of life (QoL) was measured using PCPQ subscales and total score. Mann-Whitney U, Kruskal-Wallis, and multivariate Poisson regression correlation analysis were performed. Results: The median age of patients was 8 (SD= 3.76). The study group consisted of 57 (76.0%) males and 18 (24.0%) females. Fifty parents (66.7%) have more than eight years of education and 35 (46.7%) earn less than 2 BWM. The impact values were significantly higher in male individuals in the oral symptoms (OS) domain and in individuals without caries experience in the social well-being (SW) domain (p<0.05). Conclusions: these results seem to suggest that individuals with ADS without caries experience in permanent dentitions in the SW domain and males in the OS domain had a higher impact quality of life.